Evidence for Proximity Effect in Superconductor–Organic Semiconductor–Superconductor Stacked Devices - Anna Kremen; Hagit Aviv; Yaakov Raphael Tischler; Amos Sharoni (Applied Sciences)
Coupling superconducting (SC) contacts to light-emitting layers can lead to remarkable effects, as seen in inorganic quantum-well LEDs with superconducting contacts, where an enhancement in radiative recombination was observed. Additional dramatic effects were theorized if both electrodes are SC, such as correlated emission and 2-photon entanglement. Motivated by this and by the question of whether proximity induced SC is possible in organic light-emitting materials, we studied the electronic properties of stacked SC–organic–SC devices. Our structures consisted of Nb (bottom) and NbN (top) SC electrodes and a spin-coated light-emitting semiconductor polymer, MEH-PPV. Sputtering the SC directly on the polymer causes pinholes, which we prevent by ultra-slow deposition of a 5 nm aluminum film, before depositing the top SC in situ. The Al protects the organic film from damage and pinhole formation, while preserving SC in the top electrodes due to the proximity effect between Al and NbN. Electrical transport measurements of the completed junctions indicate that indeed, the top and bottom contacts are superconducting and the protected MEH-PPV layer is pinhole-free, as supported by HR-TEM and EDS. Most importantly, we find that as the temperature is decreased below the critical temperature of the SCs, the device shows evidence for the proximity effect in the MEH-PPV.